Developing gene knockdown-replacement therapies for spinocerebellar ataxia type 7 - Curtis, H; Helen Curtis (2013)
For many dominant diseases, conventional treatment options are limited. This makes them attractive candidates for gene therapy, which may be directed to specifically silence a disease-causing allele. However, many mutations are not easily amenable to this technique, including nucleotide repeat expansions, which cause numerous neurodegenerative diseases such as Huntington’s disease and several Spinocerebellar Ataxias. Combined gene knockdown and replacement (K&R;) may present a more practical approach for such conditions, whereby the gene of interest is subject to mutation-independent non-allele-specific silencing and concurrently replaced with a functional copy. Artificial mimics of naturally occurring intronic microRNAs are theoretically ideal for this purpose, since they can be nested within the replacement gene. This thesis investigates the development of mimics of two different intronic miRNA systems (mirtron miR-1224 and the miR-106b cluster) to silence Ataxin-7 and to be incorporated into novel single K&R; constructs for testing in vitro. Artificial mirtrons and intronic miRNAs were successfully developed and shown to silence Ataxin-7 mRNA in numerous cell lines. An RNAi-resistant gene was developed and mirtrons could be successfully incorporated as introns. Patient-derived fibroblasts and iPSC-derived neuronal cells were investigated as models for testing of gene silencing therapies. This work suggests that mirtron-based K&R; is achievable, and warrants further investigation.